Editorial: The function of stories in hostile asylum regimes - Collis, Stephen (Frontiers in Political Science, 2023)
In this fictional story, a traveller from a distant land is welcomed at the end of a long journey. As part of his integration into his new home, he learns about the global project of the Population Redistribution Network. The story draws upon the tradition of utopian fiction in order to offer a glimpse of an alternative culture of immigration - one which works beyond borders and outside systems of immigration detention and deportation.